The Utilization of Rawa Pening Swamp Area for Fisheries - Su Ritohardoyo; Alip Sontosudarmo (Forum Geografi, 1997)
This article concern with the impact of the fishery ‘karamba’ system on socio-economics of fishermen in the Rawa Pening Environs. The aim of the study is to appraise the activities of fishery ‘karamba’ system. In the relationship with loccal fishermen income, and labor force employment. To some extent, the research is directed to study on income differentation based on job status as fishermen and ‘karamba’ farmers. Differentation of tools kinds for fishing, and seasonal variation. Survey method is employed in this research, whether it is for karamba farmer or local fishermen. Respondent number about 187 consists of 139 fishermen, 28 ‘karamba’ labors, and 20 ‘karamba’ farmers. Technical of tabulation and ‘t’ test statistical use for data analysis.The research shows that fishery ‘karamba’ system so much decreases on the activities, number of facilities, and it fish production. Decreasing of those are mainly caused by uncontrolled growth of ‘eceng gondok’ (Eichornia crassipes), capital constrain, and security constraint especially stealing of fish production. The existing of fishery ‘karamba’ system employs 68,00% labors are local fishermen, and 32,00% are not fishermen come from other areas. Viewed by the job opportunities most of part contribute ‘karamba’ farmers (55%) who ome from out of the area, and 45% ‘karamba’ farmer are local people. Really affect of the fishery ‘karamba’ system to the local fishermen is decreasing of fish production. Fish production of local fishermen has been lower since fishery ‘karamba’ system be carried out in this lake. Though the fish production of fishery ‘karamba’ system decreases, however income average of the ‘karamba’ farmer is higher (Rp 1,849,000/annum) than the income average of local fishermen. The average of fishermen income who using fish grasper is higher (Rp 1,401,000/annum) than the average of fishermen income who using fish trap (Rp 1,21,000/unnum) and who using fish grasper and fish trap (Rp 1,349,000/annum). Nevertheless the average of fishermen’s income is higher than ‘karamba’s’ labor (Rp 897,000). This research is also finding wether it is average production or income of the ‘karamba’ farmer are not seasonal, and those are quite difference with local fishermen. The average of fish production on dry season (825 kg) are higher than on wet season (625 kg). Therefore, the average of income on dry season are higher than that on wet season.